Inhibition of the development of N-nitrosomethylbenzylamine-induced esophageal tumors in rats by strawberries and aspirin, alone and in combination - Pan, Pan (J Berry Res, 2018)
BACKGROUND: Esophageal squamous cell carcinoma (ESCC) is one of two subtypes of esophageal cancer, with high incidence and mortality rates in developing countries. OBJECTIVE: The current study investigated the potential chemoprotective effects of strawberries and aspirin against the development of rat esophageal papillomas, the precursors to ESCC. METHODS: Using a prevention model, we administered study diets to rats before, during, and after N-nitrosomethylbenzylamine (NMBA) treatment. The effects of the four diets were evaluated: the control diet, 5% strawberry powder in the control diet, 0.01% aspirin in the drinking water, and the combination of strawberries and aspirin. At week 25, we euthanized all the rats and collected their esophagi to quantify tumor incidence, multiplicity, and burden, as well as for molecular analysis. RESULTS: Both strawberries and aspirin significantly decreased esophageal tumor multiplicity, with the combination causing the most robust suppression. Aspirin alone and the combination decreased the total tumor burden in the esophagus. None of the diets had a significant effect on tumor incidence or the expression of COX-1 and COX-2. Strawberries and aspirin, alone and in combination, significantly suppressed squamous epithelial cell proliferation (PCNA). CONCLUSIONS: Strawberries, aspirin, and their combination exhibit chemoprotective effects against NMBA-induced esophageal tumors in rats.